Reactions to threatening critical messages from minority group members with shared or distinct group identities. (22nd November 2012) - Wirtz, Coen; Doosje, Bertjan
Abstract Reactions to members of other groups are important in multicultural societies. In four studies (N = 725), we investigate the reactions of majority group members to minority group members who stress either their distinct identity or their shared identity when they express threatening critical messages. In Study 1, we investigate reactions to a person who stresses the importance of either his Moroccan and Muslim identity or his Dutch and non‐Islamic identity. In Studies 2 and 3, we disentangle national and religious identity. Across all studies, we find that minority group members who stress their shared identity rather than their distinct identity are evaluated more positively, are perceived as more similar to the self, and tend to evoke less anger. In Study 4, we replicate this finding and show that perceived similarity mediates the impact of identity on these evaluations, but constructiveness only partially mediates these relations. Results are discussed in terms of recategorization models and the intergroup sensitivity effect. Copyright © 2012 John Wiley & Sons, Ltd.